2005
DOI: 10.1038/ncb1329
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of early flowering by expression of FLOWERING LOCUS C requires methylation of histone H3 K36

Abstract: Flowering represents a crucial transition from a vegetative to a reproductive phase of the plant life cycle. Despite extensive studies, the molecular mechanisms controlling flowering remain elusive. Although the enzymes involved are unknown, methylation of histone H3 K9 and K27 correlates with repression of FLOWERING LOCUS C (FLC), an essential transcriptional repressor involved in flowering time control in Arabidopsis thaliana; in contrast, methylation of H3K4 correlates with FLC activation. Here we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
310
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(333 citation statements)
references
References 28 publications
21
310
0
2
Order By: Relevance
“…These findings suggest that histone methylation may play broad and important roles in regulating transcription. Consistent with this notion, several Arabidopsis histone methyltransferase (HMTase) mutants have been found to exhibit a myriad of developmental abnormalities (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, transcriptome profiling studies have identified numerous genes that are misregulated in HMTase mutants (19,27,28).…”
mentioning
confidence: 62%
“…These findings suggest that histone methylation may play broad and important roles in regulating transcription. Consistent with this notion, several Arabidopsis histone methyltransferase (HMTase) mutants have been found to exhibit a myriad of developmental abnormalities (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, transcriptome profiling studies have identified numerous genes that are misregulated in HMTase mutants (19,27,28).…”
mentioning
confidence: 62%
“…Further support comes from the finding of a decreased level of H3K36 methylation at the FLC gene in sdg8 mutant plants (Zhao et al, 2005).…”
Section: Histone Methylasesmentioning
confidence: 66%
“…ASHH1 is the Arabidopsis homolog of yeast Set2 [44] which has been shown to exhibit H3K36 methyltransferase activity [64]. In addition, genetic studies revealed that ashh2 mutants show an early flowering phenotype that is accompanied by a decrease in H3K36 methylation at the FLOWERING LOCUS C (FLC) [65].…”
Section: Class Ii: the Ash1 Homologs (H3k36)mentioning
confidence: 99%